Analisis Sistem Pengendalian Internal dalam Meningkatkan Penjualan Sepeda Motor Pada PT. Hasjrat Abadi Kotamobagu - Meisy Lengkung; Belthasar Trito Siahaan; Harty U. H. L. Koagouw (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the implementation of an internal control system in improving motorcycle sales at PT Hasjrat Abadi Kotamobagu. An internal control system plays an important role in supporting operational effectiveness, minimizing the risk of errors and fraud, and assisting the achievement of sales targets. The background of this research is the fluctuation in motorcycle sales, which tend to increase before major religious holidays but decline during certain periods, indicating the need for effective internal controls to maintain sales stability. This study employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The analysis is based on the five components of the internal control framework developed by the Committee of Sponsoring Organizations of the Treadway Commission (COSO), namely control environment, risk assessment, control activities, information and communication, and monitoring. The findings indicate that PT Hasjrat Abadi Kotamobagu has implemented an internal control system fairly well in its sales activities. However, several weaknesses were identified, including overlapping duties among certain employees, risks of data entry errors, and the need to improve monitoring and evaluation activities on an ongoing basis. Overall, the implementation of the internal control system has supported the improvement of motorcycle sales, although further enhancements are required to achieve greater effectiveness and efficiency.